2010
DOI: 10.1177/0018726710386396
|View full text |Cite
|
Sign up to set email alerts
|

Connecting religion and work: Patterns and influences of work-faith integration

Abstract: Religiosity can significantly impact human behavior yet little is known about how religious belief and practice integrate with work. Using the Faith at Work Scale, we surveyed Christian workers in the United States (n = 374) and found that work-faith integration was positively associated with faith maturity, church attendance, age and denominational strictness, and negatively associated with organizational size. Denominational groups varied in their degree of integration but displayed similar patterns across d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
54
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 92 publications
3
54
0
1
Order By: Relevance
“…In addition to the moderators we discussed, it seems sensible to also analyze the (moderating) effects of the type of the organization (e.g. religious/non-religious; profit/non-profit; Smith et al, 2006), the size of the organization (Lynn et al, 2010) and the type of workplace -for example, in terms of the frequency of social interaction (Davidson and Caddell, 1994). In part because the effects of these moderators are controversial (Lynn et al, 2010), we did not refer to them in our analysis.…”
Section: Limitations and Further Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the moderators we discussed, it seems sensible to also analyze the (moderating) effects of the type of the organization (e.g. religious/non-religious; profit/non-profit; Smith et al, 2006), the size of the organization (Lynn et al, 2010) and the type of workplace -for example, in terms of the frequency of social interaction (Davidson and Caddell, 1994). In part because the effects of these moderators are controversial (Lynn et al, 2010), we did not refer to them in our analysis.…”
Section: Limitations and Further Researchmentioning
confidence: 99%
“…religious/non-religious; profit/non-profit; Smith et al, 2006), the size of the organization (Lynn et al, 2010) and the type of workplace -for example, in terms of the frequency of social interaction (Davidson and Caddell, 1994). In part because the effects of these moderators are controversial (Lynn et al, 2010), we did not refer to them in our analysis. Moreover, our framework would benefit from an analysis of the effects engendered by the changes in the religion-related workforce composition (e.g.…”
Section: Limitations and Further Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Having a sense of calling is strongly related to purpose for one's life; therefore, it should also make up a considerable portion of one's self-concept. In one study of the self and transcendence, researchers found that most respondents tended to overemphasized aspects of the self as compared to aspects of transcendence or spirituality (Lynn, Naughton, & Vander Veen, 2010). The work roles that are psychologically central to our self-concept are fundamental in predicting behavior that corresponds with our identity (Farmer & Van Dyne, 2010).…”
Section: Calling As Identitymentioning
confidence: 99%
“…Integrating spirituality and work is critical because work serves the function of connecting behavior, values, and meaning for many employees (Bean, 2000;Tisdell, 2000). The workplace spirituality literature has highlighted the idea that employees bring their entire selves to work and religious identity influences work behaviors; however, the conclusions that can be drawn about how religious belief influence work have been limited (Lynn et al, 2010). Despite the limited empirical evidence, spirituality remains an important area for future research.…”
Section: Calling As Identitymentioning
confidence: 99%